Evaluation of ESMAP Regional Power Trade Portfolio - Means, Robert C. (2016)
The joint United Nations Development Program (UNDP) and World Bank Energy Sector Management Assistance Program (ESMAP) is a special global technical assistance partnership sponsored by the UNDP, the World Bank, and bi-lateral official donors. Established with the support of UNDP and bilateral official donors in 1983, ESMAP is managed by the World Bank. ESMAPs mission is to promote the role of energy in poverty reduction and economic growth in an environmentally responsible manner. Its work applies to low-income, emerging, and transition economies and contributes to the achievement of internationally agreed development goals. ESMAP interventions are knowledge products including free technical assistance specific studies advisory services, pilot projects, knowledge generation and dissemination, trainings; workshops and seminars, conferences and roundtables, and publications. ESMAP work is focused on three priority areas: access to modem energy for the poorest, the development of sustainable energy markets, and the promotion of environmentally sustainable energy practices. ESMAP has supported a number of energy trade programs, but so far feedback from these projects and evaluations of the knowledge gained has been limited. It was therefore decided to undertake a review ESMAPs portfolio of projects related to the international trade of energy. This review was to include not only those projects that have been completed, but also those that currently are under way, and those that are in the immediate pipeline. The review was guided by the technical advisory group to the energy trust funded programs located at the World Bank.